Clouds of witnesses : Christian voices from Africa and Asia - Noll, Mark A., 1946- (IVP Books, 2011)
In seventeen narratives Mark Noll and Carolyn Nystrom introduce Christian leaders in Africa and Asia who had tenacious faith in the midst of deprivation, suffering and conflict. Spanning a century, from the 1880s to the 1980s, their stories demonstrate the vitality of the Christian faith in a diversity of contexts. --from publisher description